If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(3b + -2) = 0 Reorder the terms: -3(-2 + 3b) = 0 (-2 * -3 + 3b * -3) = 0 (6 + -9b) = 0 Solving 6 + -9b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -9b = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -9b = 0 + -6 -9b = 0 + -6 Combine like terms: 0 + -6 = -6 -9b = -6 Divide each side by '-9'. b = 0.6666666667 Simplifying b = 0.6666666667
| -5/5i | | 4/5y-20=160 | | 22x=23x-1 | | 8X=7X-21 | | 5-11=-3z | | 7(5x-4)-(5+7x)= | | 4r-p=q | | 12g=24 | | 9(6-5x)-2(3+6x)= | | 5(3x-2)=(2x-1) | | g(x)=3-9x | | 9(8+5m)= | | -8v+3(v+3)=14 | | 4(9x+8)-9(6-3x)= | | (x+4)(x+2)-3=0 | | (8x-4)+92=180 | | f(x)=x-17 | | 5(7x-8)-6(12x-4)= | | y=-9+5 | | 60+8x=80+6x | | 36x^2+16y^2+9z^2-144=0 | | 3z+5z-7z=7 | | 3/5x-7 | | 9(w+3)=3w+15 | | 6(3x-3)-(4+5x)= | | 2a-3=-5a+11 | | (fx)=2x-6 | | f(x)=x^2-10x+8 | | 25-64z^2=0 | | 20q-4q+q-15q=18 | | 420=16x*16x+27x | | 6(7x-3)-6(4-3x)= |